2019
DOI: 10.1186/s12884-019-2306-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing ultraviolet B radiation exposure to prevent vitamin D deficiency among pregnant women in the tropical zone: report from cohort study on vitamin D status and its impact during pregnancy in Indonesia

Abstract: Background Vitamin D deficiency during pregnancy carries potential threat to fetal well being. Natural conversion of vitamin D in the skin can be facilitated by direct ultra violet B (UVB) radiation, but the effect is reduced by wearing umbrellas, clothes, or sunblock cream. Muslim women wear hijab that allows only face and hands to be seen. With increasing proportion of muslim women wearing hijab and the lack of vitamin D fortification and fish consumption in Indonesia, it poses a problem for vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 41 publications
(41 reference statements)
5
23
0
3
Order By: Relevance
“…As such, there are recommendations for pregnant women relating to sun exposure in Indonesia, i.e. continuous sun exposure between 10 am to 1 pm for 30 minutes (or 60 minutes for veiled women) per day [31]. The findings here support the recommendations that pregnant women have adequate sun exposure, as higher sun exposure reduced the risk of vitamin D deficiency at birth.…”
Section: Plos Onesupporting
confidence: 71%
“…As such, there are recommendations for pregnant women relating to sun exposure in Indonesia, i.e. continuous sun exposure between 10 am to 1 pm for 30 minutes (or 60 minutes for veiled women) per day [31]. The findings here support the recommendations that pregnant women have adequate sun exposure, as higher sun exposure reduced the risk of vitamin D deficiency at birth.…”
Section: Plos Onesupporting
confidence: 71%
“…The estimation of dietary intake, sunlight exposure, and sunscreen use are approximations. Nevertheless, our findings are in line with previous studies in Indonesia [9,10], strengthening the epidemiological evidence that VDD is prevalent in Indonesian women, and the lack of sunlight exposure is an essential determinant for VDD. Fig.…”
Section: Discussionsupporting
confidence: 92%
“…A study in Kenya, a tropical country, showed that 51% of women had insufficient (< 75 nmol/L), and 21% had deficient serum 25(OH)D level (< 50 nmol/L) [8]. With the high prevalence of VDD in women reported in sunny countries [8][9][10], VDD in pregnant women needs particular attention because of the potential unwanted birth outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The provision of vitamin D supplementation in Indonesia is still difficult as a standard due to the high price. As an alternative, exposing 18.59% of body surface area to sunlight for 37.5 minutes per day especially between 10.00−13.00 is proven to be an effective method to meet daily vitamin D requirements, as reported by Judistiani et al 25 The limitation of this study was not report, several factors that could have affected vitamin D levels and neurodevelopmental status at the age of two year old, such as parenting style and complementary food given after the age of 6 months old. Future long-term cohort studies taking these factors into consideration or randomized clinical trial giving vitamin D supplementation is required.…”
Section: Discussionmentioning
confidence: 93%